The history of South Vietnam - Lâm, Vĩnh-Thế, author.
1 online resource
Keywords: This book provides an in-depth analysis of the political instability of South Vietnam between the two Republics and offers a valuable contribution to the study of the history of Vietnam as it focuses on a decisive period in the history of South Vietnam. A much-needed examination of the political environment of the Republic of Vietnam between 1963-1967, this book shows how South Vietnamese leadership failed to form a stable civilian government and to secure South Vietnam against the increasing threat by North Vietnam. Through a detailed assessment of political difficulties during the period, the book suggests that, to prevent the imminent loss of South Vietnam to the Communist forces, the United States government did not have any other option than to escalate the war by committing its combat ground forces in the South and beginning the sustained bombing in the North. Moreover, the book analyses the administration of General Khánh and Prime Minister Phan Huy Quát and includes a full account of the War Cabinet of General Nguy¿n Cao K̤. The achievements, the difficulties and the sudden death of the National High Council as well as the confrontation between the Buddhists and the Trʹn Vãn Hýõng government are also explored. This book will be of interest to researchers and students of the contemporary history of Vietnam, the history of the Republic of Vietnam, the Vietnam War and Southeast Asian history and politics.--